Privatisation of Agricultural Advisory Services and Consequences for the Dairy Farmers in the Mantaro Valley, Peru - Faure, G.; Huamanyauri, M.K.; Salazar, I.; Gomez, C.; de Nys, E.; Dulcire, M. (Taylor and Francis, 2017)
The private sector’s presence in agricultural advisory services worldwide has been on the increase for over three decades. This trend has also been observed in the Mantaro Valley (Peru), in a context of dairy family farming. The objective of the article is to analyse the modalities of advisory services privatization and assess the consequences of this privatization for the farmers and their livestock systems. The activity of private advisers is most often associated with the sale of livestock inputs which leads to an increase of production costs and does not take the overall producer needs into account. However, in line with the development of mobile phones, private advisory services are facilitating access to technical support for almost all producers. Public advisory services are less active and still focus on the use of inputs without adapting their services to the evolution of the advisory system.